Modern Approaches to Rheumatic Carditis in Children - Olonazarovich, Jumayev Ravshan; Karimovna, Xusainova Venera (American Journal of Biomedicine and Pharmacy, 2024)
In modern rheumatology, the timely and accurate diagnosis of acute rheumatic fever (ARF) remains a significant issue. The variety of forms and courses (clinical polymorphism), the blurring of clinical and laboratory symptoms, and the lack of specific tests for ARF often serve as sources of both underdiagnosis and overdiagnosis in clinical practice. The relevance of this issue is also linked to the identification of new nosological forms that share similar clinical symptoms with ARF but require fundamentally different therapeutic approaches.